2020
DOI: 10.1139/cjpp-2019-0290
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different concentrations of desflurane on the index of cardiac electrophysiological balance in gynecologic surgery patients

Abstract: The objectives were to observe the effects of different concentrations of desflurane on QT, QTc, Tp-e, Tp-e/QT, and the index of cardiac electrophysiological balance (iCEB). Sixty patients were randomly divided into group D1, group D2, and group D3 by using a random number table, 20 in each group. After entering the operating room, patients received 10 mL/kg hydroxyethyl starch, 0.1 mg/kg midazolam, 0.1 mg/kg vecuronium, 3 μg/kg fentanyl, and 0.3 mg/kg etomidate intravenously and then accepted intubation and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The use of some medications, such as β-blockers or β 1 -and β 2 -adrenoreceptor agonists, increases iCEB [14,15]. Importantly, anesthesia with desflurane does not affect the iCEB [39]. In the present study the mean iCEB value oscillated around 4.…”
Section: Discussionsupporting
confidence: 38%
“…The use of some medications, such as β-blockers or β 1 -and β 2 -adrenoreceptor agonists, increases iCEB [14,15]. Importantly, anesthesia with desflurane does not affect the iCEB [39]. In the present study the mean iCEB value oscillated around 4.…”
Section: Discussionsupporting
confidence: 38%
“…iCEB is an index that can reflect cardiac electrophysiological balance quickly and intuitively, which predicts the risk of arrhythmias, including torsades de pointes (TdP) and non-TdP ventricular tachycardia/ventricular fibrillation [ 28 , 29 ]. The higher the iCEB values, the more likely imbalanced the electrophysiological homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Any prolongation in Tpe interval effects the excitation and conduction, and induces TdP. In the study of Liu et al the effect of desflurane on Tpe interval in three groups with different MAC values at the same FGF rates was investigated and no significantly different prolongation was reported 20 . The authors concluded that desflurane does not have an effect on ventricular transmural dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of Tpe/QT is the ratio of relative to total ventricular refractory period. The higher the ratios the higher proportion of the relative refractory period, so the higher probability of cardiac electrical re-entry 20 . The ratio of Tpe/QT helps us to predict ventricular arrhythmia risk without the effect of HR20 and this why we preferred the Tpe/QTc ratio, as QTc is more reliable than QT.…”
Section: Discussionmentioning
confidence: 99%